2018
DOI: 10.1111/jace.16158
|View full text |Cite
|
Sign up to set email alerts
|

Co2P2O7–Ni2P2O7 solid solutions: Structural characterization and color

Abstract: NH4[Co1−yNiyPO4]·H2O (0 ≤ y ≤ 1) single crystals were fired to prepare Co2−xNixP2O7 0 ≤ x ≤ 2 solid solutions between 800 and 1200°C. The structure of these solid solutions is α‐M2P2O7 (M = Co, Ni). The contraction of the unit cell with increasing x confirmed the formation of these solid solutions. The UV–vis–NIR spectra of these solid solutions were consistent with Co(II) and Ni(II) ions in the two different crystallographic sites (octahedral site and square pyramidal site) in the α‐M2P2O7 structure. Due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The values of b*(+), amount of yellow colouration, in compositions with 0.3 ≤ x ≤ 1.2 are high. The b* = + 50.93 value obtained from the Mg 0.5 Cu 1.5 V 0.9 P 1.1 O 7 (x = 0.9) composition fired at 600 °C is comparable to the b* = 55.52 value obtained from Ni 2 P 2 O 7 fired at 1000-1200 °C [31] and better than the b* = 47.81 from Ni 2 V 2 O 7 fired at 600 °C [32]. In these compositions, the majority crystalline phase presents the α-Cu 2 P 2 O 7 structure.…”
Section: Resultssupporting
confidence: 65%
“…The values of b*(+), amount of yellow colouration, in compositions with 0.3 ≤ x ≤ 1.2 are high. The b* = + 50.93 value obtained from the Mg 0.5 Cu 1.5 V 0.9 P 1.1 O 7 (x = 0.9) composition fired at 600 °C is comparable to the b* = 55.52 value obtained from Ni 2 P 2 O 7 fired at 1000-1200 °C [31] and better than the b* = 47.81 from Ni 2 V 2 O 7 fired at 600 °C [32]. In these compositions, the majority crystalline phase presents the α-Cu 2 P 2 O 7 structure.…”
Section: Resultssupporting
confidence: 65%
“…In σ-M 2 P 2 O 7 , the single octahedral and tetrahedral crystallographic sites of M and P are similar to those in β-M 2 P 2 O 7 . Detailed bond lengths and variations in sizes due to the transformation from α → β and σ-M 2 P 2 O 7 were reported by Tena et al 52 Similarly, the change from α → β-NaCoPO 4 at elevated temperature was reported by Chiring et al 53…”
Section: Correlations Between Structure and Charge Storage In Tmpsmentioning
confidence: 68%
“…The smaller triangular shape, linked by three (M 4 O 12 ) n chains, is occupied by 2/8 tetrahedral groups of HPO 3 , whereas the larger occupies the other (6/8) phosphite groups situated on the walls of hexagonal networks. 50,51 Tena et al 52 explained the metal pyrophosphate phase transition on increasing temperature. The α-M 2 P 2 O 7 (M = Co, Ni) monoclinic structure crystallizes in the P 12 1 / c space group with Z = 4 (number of unit formulae in the unit cell) and is stable at room temperature, and all atoms are situated at 4e sites.…”
Section: Correlations Between Structure and Charge Storage In Tmpsmentioning
confidence: 99%
“…At 1200 °C, the charge transfer band of Cu(II)-O is observed around 400 nm. The high asymmetry observed in all the bands is due to the difference in Ni-O (between 1.982 and 2.181 Å) and Cu-O distances (between 1.924 and 2.259 Å) in the Ni 3 P 2 O 8 and Cu 3 P 2 O 8 structures (ICSD-153159 and ICSD-1143 [5]). Structural distortion due to the Jahn-Teller effect also contributes to the asymmetry in the observed bands obtained from the Cu 3 P 2 O 8 composition.…”
Section: Methodsmentioning
confidence: 93%
“…The absence of a charge transfer band in the visible wavelength range explains the pale blue or weak greenishblue colourations in Cu 2 P 2 O 7 and Cu 3 P 2 O 8 compounds. Strong absorbance due to charge transfers is the most important component in the colouration of some materials [4][5][6]. The Ni(II) orthophosphate structure is stable with temperature and in a commercial glaze and can be used as a yellow ceramic pigment in industry [4].…”
Section: Introductionmentioning
confidence: 99%